2013
DOI: 10.1080/08870446.2012.745935
|View full text |Cite
|
Sign up to set email alerts
|

Closing the intention–behaviour gap for sunscreen use and sun protection behaviours

Abstract: Objective: Two studies were conducted with the aim of closing the intentionbehaviour gap for sunscreen use and sun protection behaviours by examining the influence of self-regulatory capacity on the prediction of sunscreen use (Study 1) and self-regulatory capacity and habit on sun protection behaviours (Study 2).Design: Studies were conducted online. Participants completed questionnaires and cognitive measures at time one and reported behaviour one week later. Main Outcome Measures:Questionnaires measuring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…These findings support the targeting of automatic alongside deliberative processes and are consistent with phase models of behaviour, which include volitional and motivational constructs [e.g., Health Action Process Approach, (Schwarzer, )]. Previous studies of photoprotection behaviour in student samples have reported positive relationships (Allom et al ., ) as have adherence studies in other chronic conditions (Durand et al ., ; Phillips, Cohen, Burns, Abrams, & Renninger, ). The development of habitual photoprotection could contribute to the negative association between age at the time of diagnosis and adherence in adults.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings support the targeting of automatic alongside deliberative processes and are consistent with phase models of behaviour, which include volitional and motivational constructs [e.g., Health Action Process Approach, (Schwarzer, )]. Previous studies of photoprotection behaviour in student samples have reported positive relationships (Allom et al ., ) as have adherence studies in other chronic conditions (Durand et al ., ; Phillips, Cohen, Burns, Abrams, & Renninger, ). The development of habitual photoprotection could contribute to the negative association between age at the time of diagnosis and adherence in adults.…”
Section: Discussionmentioning
confidence: 93%
“…Adherence in the cared‐for sample was higher than in the adults, which could be explained by the impact of having somebody monitoring and helping patients to meet their health needs. Whilst this could potentially be a reporting bias, a number of psychological correlates exhibited by caregivers are consistent with those found to be more favourable to adherence to photoprotection in other populations including higher self‐efficacy (Craciun, Schüz, Lippke, & Schwarzer, ), stronger intention (Starfelt Sutton & White, ), and greater automaticity (Allom et al ., ). Although the cared‐for sample reported higher photoprotection, social support, in terms of both the perceived level and quality of support, in the whole sample was not related to adherence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Various surveys show that the awareness of the need to be sun-safe, intentions to prevent sunburns (Allom, Mullan, & Sebastian, 2013; Araujo-Soares, Rodrigues, Presseau, & Sniehotta, 2013; Geller, Cantor, et al, 2002; Geller, Colditz, et al, 2002; Heckman & Coups, 2011), as well as self-reported sun-protection behaviours are increasing over time (Cancer Research UK, 2009; Centers for Disease Control and Prevention, 2012). However, contrary to the focus of public health messages of seeking shade and using protective clothing, the most frequently reported sun-protection behaviour in population surveys is the use of sunscreen.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, individuals with poor inhibition are less likely to eat healthy foods (Limbers & Young, 2015; Segerstrom & Nes, 2007) or engage in healthy amounts of physical activity than those with high inhibition, even when they have the intention of doing so (Hall, Fong, Epp, & Elias, 2008). Those with poor inhibition are less likely to consume fruits/vegetables (Allom & Mullan, 2014), adhere to a weight loss plan (Pauli-Pott, Özgür, Hebebrand, & Pott, 2010), utilize sunscreen (Allom, Mullan, & Sebastian, 2013), or demonstrate adaptive sleeping habits than those with better inhibition (Kor & Mullan, 2011). Impaired inhibition also leads to alcohol relapse following treatment (Gardland, Franken, & Howard, 2012).…”
Section: Discussionmentioning
confidence: 99%